Peran SIMKARI dalam Meningkatkan Transparansi dan Akuntabilitas Kejaksaan di Era Digital pada Kejaksaan Tinggi Gorontalo - Sri Yulianty Mozin; Khairunnisa Ahmad; Selvia Ningsi Panigoro; Wulandari Putri Radjak; Fadillah Abdullah; Indriyani Lumentut; Rahmatia Pakaya (Pusat Riset dan Inovasi Nasional, 2025)
This research examines the role of SIMKARI (Sistem Informasi Manajemen Kejaksaan) in enhancing transparency and accountability at the High Prosecutor’s Office of Gorontalo in the digital era. The implementation of SIMKARI, as a digital management information system, is aimed at improving the efficiency of data management, monitoring, and reporting within the institution. Through qualitative research methods including literature study, observation, and interviews with key stakeholders at the High Prosecutor’s Office of Gorontalo, this study identifies both the benefits and challenges associated with SIMKARI's use. The results indicate that SIMKARI has significantly contributed to the transparency of public information and the accountability of internal performance. However, challenges such as limited digital literacy and infrastructure issues remain. The study concludes that continuous improvement and strategic collaboration are necessary to optimize SIMKARI’s effectiveness in supporting a transparent and accountable justice system.